Escritórios de planta livre: o impacto de diferentes soluções de fachada na eficiência energética - Brugnera, R. (2019)
In Brazil, open-plan office buildings are increasingly using fully glazed facades, an aspect that can directly impact air-conditioning consumption. Thisstudy aims at classifying and characterising the energy performance of open-plan office buildings in three Brazilian climates. Computational simulations were performed in the EnergyPlus program to verify the impact of various parameters (climate, type of facade, WWR, type of glass, shading device and setpoint temperature) on air-conditioning consumption. The results, classified in energy performance levels, showed that changing from traditional facades (masonry) to curtain facades (fully glazed), increased energy consumption with air-conditioning by an average of 25% in Curitiba and São Paulo and 15% in Manaus; the WWR was the parameter that most impacted this consumption, and the glass type had most impact in the larger openings; using a shading device always generated savings and a 1°C increase in the cooling setpoint reduced consumption by an average of 16.4%. The results allowed to identify the best combinations of these parameters for each climate which can help designers to create more energy efficient buildings.